Thermal properties of size-selective nanoparticles: Effect of the particle size on Einstein temperature. (May 2016) - Li, Y; Anderson, R M; Duan, Z; Chill, S; Crooks, R M; Henkelman, G; Frenkel, A I
Abstract: Characterizing size related thermal properties of nanoclusters is challenging due to the requirement to accurately control both their average sizes and the size distributions. In this work, temperature-dependent Extended X-ray Absorption Fine Structure spectroscopy and the phenomenological bond-order-length-strength (BOLS) model were employed to investigate the size-dependent Einstein temperature of Au nanoclusters. Theoretical calculations of Einstein temperature and average bond distance for clusters with different sizes agree quantitatively with experiment. The BOLS model is thus useful for predictive understanding of structure and thermal properties in well-defined metal clusters.